Development of a New Plasmonic Transducer for the Detection of Biological Species - Laffont, Emilie (Université d'Ottawa / University of Ottawa, 2024)
During the COVID-19 outbreak, PCR tests were widely used for large-scale testing and screening. Yet, this technique requires bulky and time-consuming procedures to prepare the samples collected from the patients before their analysis by well-trained experts with expensive and specific equipment. PCR is therefore not competitive as a technique of detection for a widespread and rapid use in point-of-care sites. Thus, the COVID-19 pandemic highlighted the need for cheap and easy-to-implement biosensors. Surface plasmon resonance based sensors were suggested as a promising alternative in recent years. Indeed, they enable real-time and label-free detection of a wide range of analytes. That explains their widespread use in various fields of applications such as pharmacology, toxicology, food safety, and diagnosis. This thesis proposes and demonstrates a new plasmonic configuration of detection, which can address challenges posed by point-of-care settings. The gratings used as transducers in this configuration were fabricated based on laser interference lithography combined with a nanoimprinting process. The responses of these nanostructures interrogated by a p-polarized light beam result in a transfer of energy between two diffracted orders over an angular scan. This optical phenomenon termed as “optical switch”, was theoretically and experimentally investigated and optimized. The principle of detection based on this specific configuration was demonstrated for the detection of small variations in the bulk refractive index with solutions comprised of different ratios of de-ionized water and glycerol. A limit of detection in the range of 10−6 RIU was achieved. In addition, preliminary bio-assays obtained by combining this configuration with a functionalization are presented and demonstrate the selectivity and the potential of this new plasmonic configuration for biosensing applications. This thesis work paves the way for the use of the optical switch configuration as a biosensor aligned with low-cost manufacturing and relevant for diagnosing in point-of-care sites.
Keywords: Surface plasmon resonance; Biosensor; Diffraction gratings; Functionalisation